Design and Build a Goods Demand Forecasting Application using the Simple Averages Method at PT Cahaya Surya Jaya Sentosa - Sugianto, Christananda Manuel; Widana Putra, I Gusti Ngurah Alit; Soebijono, Tony Soebijono S (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
PT Cahaya Surya Jaya Sentosa Demands for goods (sales) is the driving factor of a company. If the company can meet customer demand well, then the company can run well. The company should be able to provide the goods for sale of the next period. PT Cahaya Surya Jaya Sentosa is a distributor of Lang Balm that provides three kinds of balsam, namely 10gram, 20gram, and 40gram. PT Cahaya Surya Jaya Sentosa serves 1500 stores with detail of 225 wholesalers, 450 semi wholesalers (self-service), and 825 retail. With a considerable demand scale, the company has problems in determining the number of products (goods) for the next period of sales. By using System Development Life Cycle (SDLC) method, it is expected to build an application that can predict the demand for goods at PT Cahaya Surya Jaya Sentosa. The algorithm used in forecasting is the simple averages method. Simple averages use a number of new demand actual data to generate forecast values for future requests